Insights into the Structure and Pharmacology of the Human Trace Amine‐Associated Receptor 1 (hTAAR1): Homology Modelling and Docking Studies. (28th March 2013) - Cichero, Elena; Espinoza, Stefano; Gainetdinov, Raul R.; Brasili, Livio; Fossa, Paola
<x xml:space="preserve">Abstract</x> Trace amine‐associated receptor 1 (TAAR1) is a G protein–coupled receptor that belongs to the family of TAAR receptors and responds to a class of compounds called trace amines, such as β‐phenylethylamine (β‐PEA) and 3‐iodothyronamine (T1AM). The receptor is known to have a very rich pharmacology and could be also activated by other classes of compounds, including adrenergic and serotonergic ligands. It is expected that targeting TAAR1 could provide a novel pharmacological approach to correct monoaminergic dysfunctions found in several brain disorders, such as schizophrenia, depression, attention deficit hyperactivity disorder and Parkinson's disease. Only recently, the first selective TAAR1 agonist RO5166017 has been identified. To explore the molecular mechanisms of protein–agonist interaction and speed up the identification of new chemical entities acting on this biomolecular target, we derived a homology model for the hTAAR1. The putative protein‐binding site has been explored by comparing the hTAAR1 model with the β2‐adrenoreceptor binding site, available by X‐ray crystallization studies, and with the homology modelled 5HT1A receptor. The obtained results, in tandem with docking studies performed with RO5166017, β‐PEA and T1AM, provided an opportunity to reasonably identify the hTAAR1 key residues involved in ligand recognition and thus define important starting points to design new agonists.